Relationships Between the Intake of n-3 Polyunsaturated Fatty Acids by Hens and the Fatty Acid Composition of Their Eggs - Bavelaar, F.J.; Beynen, A.C. (International Journal of Poultry Science, 2004)
The objective of this literature survey was to establish the relationships between fatty acid intake of hens and the fatty acid composition of their eggs. The content of eicosapentaenoic acid (EPA) of egg yolk was not clearly influenced by alpha-linolenic acid intake, but there was a linear relationship with EPA intake albeit that the efficiency of incorporation was very low. Maximum egg yolk contents of docosahexaenoic acid (DHA) of about 1.5% of total fatty acids were attained at a dietary alpha-linolenic acid concentration higher than 7% of total fatty acids. Dietary DHA was found to be efficiently incorporated into egg yolk. There were linear relationships between dietary alpha-linolenic acid and linoleic acid and their contents in egg total lipids. The relationships presented, including the regression equations, may assist in the diet-mediated steering of the fatty acid composition of eggs.